Temporal proteomic profiling reveals functional pathways in vaccinia virus-induced cell migration - Lu, Jiayin; Liu, Wei; Chen, Xue-Zhu; Wang, Yiwen; Ying, Tianlei; Qiao, Liang; Liu, Yan-Jun; Liu, Baohong (Frontiers in Microbiology, 2023)
Introduction Viral diseases have always been intricate and persistent issues throughout the world and there is a lack of holistic discoveries regarding the molecular dysregulations of virus-host interactions. The temporal proteomics strategy can identify various differentially expressed proteins and offer collaborated interaction networks under pathological conditions. Method Herein, temporal proteomics at various hours post infection of Vero cells were launched to uncover molecular alternations during vaccinia virus (VACV)-induced cell migration. Different stages of infection were included to differentiate gene ontologies and critical pathways at specific time points of infection via bioinformatics. Results Bioinformatic results showed functional and distinct ontologies and pathways at different stages of virus infection. The enrichment of interaction networks and pathways verified the significances of the regulation of actin cytoskeleton and lamellipodia during VACV-induced fast cell motility. Discussion The current results offer a systematic proteomic profiling of molecular dysregulations at different stages of VACV infection and potential biomedical targets for treating viral diseases.